The Role of Psychologists in Treating Pelvic Pain Conditions - Gernand, Anna K.; Allen, Darrielle L.; Lupe, Stephen E.; Simons, Madison L. (Clinics in Colon and Rectal Surgery, 2025)
Patients with pelvic floor disorders may experience a wide range of symptoms affecting one or more compartments of the pelvic floor (anterior/urinary, apical/reproductive, and posterior/gastrointestinal). Disorders affecting the pelvic organs (e.g., endometriosis, IBS), nerves, and supportive musculature (e.g., pelvic floor dysfunction, muscle trauma) often co-occur. As a result, individuals with one or more of these conditions may fluctuate between or simultaneously experience symptoms such as pelvic pain, urinary frequency/urgency/incontinence, sexual dysfunction, and gastrointestinal problems. This multifaceted range of symptoms results in the need for interdisciplinary team-based approaches to tailor treatment. Given the negative impact pelvic floor symptoms can have on quality of life and mental health which in turn can “turn up the dial” on the severity of symptoms, psychologists play an integral role in optimizing care for the whole patient. The rationale for and role of the psychologist in treating gastrointestinal and urogynecological symptoms will therefore initially be discussed according to symptom cluster after which the scope for a transdiagnostic treatment approach will be explored.
Keywords: pelvic pain; behavioral health; psychological treatment; trauma